Convergence Results for Proximal Point Algorithm in Complete Cat(0) Space for Multivalued Mappings - Samir Dashputre; C. Padmavati; Kavita Sakure (Journal of the Indonesian Mathematical Society, 2021)
In this paper, we propose the modified proximal point algorithm with the process for three nearly Lipschitzian asymptotically nonexpansive mappings and multivalued mappings in CAT(0) space under certain conditions. We prove some convergence theorems for the algorithm which was introduced by Shamshad Hussain et al. [18]. A numerical example is given to illustrate the efficiency of proximal point algorithm for supporting our result.